ANALISIS KINERJA KEUANGAN BANK SYARIAH DI BEI DENGAN INDIKATOR NON-PERFORMING FINANCING DAN FINANCING TO DEPOSIT RATIO - Sari, Intan Mayang; Hak, Nurul; Hariyadi, Rizky (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to analyze the financial performance of Islamic banks listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period using Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) indicators. The research method used is a descriptive quantitative approach with secondary data in the form of annual financial reports obtained from the official IDX website. The results show that, in general, all banks were able to maintain their NPF ratios in the healthy to very healthy category according to Bank Indonesia criteria. Bank Syariah Indonesia recorded a downward trend in NPF from 2.94% (2021) to 1.90% (2024), while Bank Aladin Syariah maintained a very low NPF in the range of 0-0.04%. BTPN Syariah and Bank Panin Dubai Syariah were in the healthy category despite experiencing fluctuations. Meanwhile, FDR performance showed variations: Bank Syariah Indonesia experienced a positive increase towards the optimal ratio (73.22%-84.85%), BTPN Syariah was consistently in the fairly healthy category, while Bank Aladin Syariah and Bank Panin Dubai Syariah experienced significant fluctuations indicating challenges in liquidity management. Keywords: Financial performance, Islamic Banking, Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR).